Exploring Challenges in the English as a Foreign Language Learning Process in Primary Schools Arising from Cultural Diversity - Nasution, Ismail Saleh; Kharisma, Adib Jasni; Ginting, Pirman (TELL - US JOURNAL, 2024)
This study examines the perspectives and experiences of the researcher, elementary school English educators, students, and parents with regard to the challenges associated with learning English as a foreign language, particularly in the context of cultural factors. It also investigates potential strategies to incorporate cultural elements into the English learning process to enhance its efficacy. This research adopts a multi-paradigm transformative approach, employing methodologies such as Critical Autoethnography, Inquiry through Writing, postmodern interview-based interviews, and document and literature review. The findings of this study reveal that both the researcher and teachers acknowledge a significant relationship between culture and the process of learning English, suggesting that integrating aspects of diverse cultures into English language instruction holds promise as a novel approach to facilitate English language acquisition within elementary school settings.